Spatial Separation and Working Memory Capacity Affect Selective Visual Attention in the Periphery - Klatt, Stefanie; Smeeton, Nicholas J. (Frontiers in Psychology, 2021)
The current study aimed to examine the effects of spatial separation and working memory capacity on selective visual attention. We investigated differences in the ability to identify the two covertly attended stimuli that appeared either along one of the meridians (e.g., both along the horizontal) or along two of the meridians (e.g., one along the horizontal and one along the vertical) in the attention-window task. Two visual stimuli in the periphery could be perceived along wider extents of the attentional focus’ meridians (horizontal, vertical, diagonal) when they were located along the same meridian (e.g., horizontal) compared to two different ones (e.g., horizontal and vertical). Subjects with high working memory capacity outperformed subjects with lower working memory capacity in both conditions and stimuli presented on two meridians were less accurately perceived. The findings support the proposal that individual differences in working memory capacity are important for selective spatial visual attention.